La función de defensa del privilegio entre el antiguo y el nuevo régimen - Beatriz Cárceles de Gea (Mélanges de la Casa de Velázquez, 2003)
This article analyses the legal principle of privilege as expressed in its most important function —the judicial defence of the subject— as generally understood in the legal and political order of the ancien regime. This was a natural defence apparent in the nexus between the ordinary law of the royal courts and the privileged jurisdictions, and as such it gainsays the accusation of judicial discrimination blandished by liberal ideology as delegitimising the legal order of the ancien regime. An examination of this function provides insights into the elements of continuity persisting through the revolution and into the new common judicial system, undermining the claim of the new ideology to have eliminated privilege.